Analysis of new agent spring rolls location to improve product sales - Khoirul Hidayat; Elva Nafisa Nurwadhika; M Fuad FM (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The lumpia dowo industry is an industry that produces spring rolls with various flavors and has 26 agents. However, with the COVID-19 pandemic, sales have decreased, so it is necessary to research the strategy of selling dowo spring rolls. One approach that can be done is to add new agents. The method used in this research is Analytical Network Process because this method can determine the best alternative agent location by displaying the ranking priority order. The results of this study indicate that there are several clusters, namely market potential, accessibility, labor, marketing reach, trust. The new agent has three alternative locations, namely Lamongan, Jombang, Bojonegoro, and Malang. The analysis results show that Jombang is the first best alternative with a value of 1, Lamongan 0.600, Malang 0.474, and Bojonegoro 0.423. So that by establishing a new agent in Jombang City, you can increase the sales of spring rolls.